Changes in intrinsic functional brain networks following blast-induced mild traumatic brain injury. (26th August 2013) - Vakhtin, Andrei A.; Calhoun, Vince D.; Jung, Rex E.; Prestopnik, Jillian L.; Taylor, Paul A.; Ford, Corey C.
Abstract: Objective : Blast-induced mild traumatic brain injuries (mTBI) commonly go undetected by computed tomography and conventional magnetic resonance imaging (MRI). This study was used to investigate functional brain network abnormalities in a group of blast-induced mTBI subjects using independent component analysis (ICA) of resting state functional MRI (fMRI) data. Methods : Twenty-eight resting state networks of 13 veterans who sustained blast-induced mTBI were compared with healthy controls across three fMRI domains: blood oxygenation level-dependent spatial maps, time course spectra and functional connectivity. Results : The mTBI group exhibited hyperactivity in the temporo-parietal junctions and hypoactivity in the left inferior temporal gyrus. Abnormal frequencies in default-mode (DMN), sensorimotor, attentional and frontal networks were detected. In addition, functional connectivity was disrupted in six network pairs: DMN–basal ganglia, attention–sensorimotor, frontal–DMN, attention–sensorimotor, attention–frontal and sensorimotor–sensorimotor. Conclusions : The results suggest white matter disruption across certain attentional networks. Additionally, given their elevated activity relative to controls', the temporo-parietal junctions of blast mTBI subjects may be compensating for diffuse axonal injury in other cortical regions.